The Effect of Motivation on Employee Performance in Cooperative Organizations - Gautam, Ramesh Prasad (Journal of Entrepreneurship & Management Studies, 2025)
This study intends to analyze the effect of motivation on the performance of the employees in the selected cooperative organizations within the Karnali province. In particular, it assesses how the performance of employees can be affected by the presence of major motivational factors such as salary and rewards, training opportunities, involvement in decision-making, and working conditions. Quantitative research methodology and structured questionnaires were used to gather firsthand data on the employees of cooperative organizations in the Karnali Province. The sample was chosen through a convenience sampling method with 380 employees. Descriptive statistical analysis was applied to SPSS 26 and Smart PLS to compute the relationship between motivation and employee performance using descriptive and inferential statistics to provide accurate and reliable results. The results suggest that independent variables such as salary and rewards, the involvement in the decision-making process, and working environment have a strong positive effect on the dependent variable, which is the employee performance. This study concluded that remuneration and rewards are very essential in motivating employees and their performance, and the monetary incentives are a powerful motivator of job commitment. Employee performance in cooperatives is greatly affected by the salary and rewards, involvement in the decision-making process, and favorable working environment. Competitive salaries and incentives increase motivation, job satisfaction and retention. Engaging employees in the decision-making process instills a feeling of ownership, commitment and creativity resulting in improved problem-solving and collaboration. A good working environment will provide physical and psychological health, which will decrease stress and turnover and increase cooperation and involvement. When properly handled, cooperative employees will be more committed, productive, and creative, which will finally result in success of the organization.